Substitution of some species-level names in the tribe Hygrotini Portevin, 1929 (Coleoptera: Dytiscidae: Hydroporinae) - Fery, Hans (Zootaxa, 2017)
Recently, Villastrigo et al. (2017b) published a new classification of the species of the tribe Hygrotini (subfamily Hydroporinae) based on a thorough phylogenetic investigation using molecular as well as morphological data (Villastrigo et al. 2017a).